(Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A - Bordine, Burton W; Wilson, Linda A; Siesser, William G (Supplement to: Bordine, BW et al. (2005): Data report: Eocene foraminifers, biostratigraphy, and paleobathymetry, Leg 197 Hole 1206A, North Central Pacific Ocean. In: Duncan, RA; Tarduno, JA; Davies, TA; Scholl, DW (eds.) Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 197, 1-4, https://doi.org/10.2973/odp.proc.sr.197.004.2005, 2005)
A sparse, predominantly benthic foraminiferal assemblage extracted from the lower volcaniclastic interval on the Koko Seamount, Leg 197 Hole 1206A, indicates an early to middle Eocene age and, in general, a middle to upper bathyal paleobathymetry (400-1000 m). The very rare occurrence of poorly preserved planktonic foraminifers tends to support this biostratigraphic interpretation, which is based primarily on benthic foraminifers.